The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1016/s1388-9842(02)00116-2
|View full text |Cite
|
Sign up to set email alerts
|

Annual rates of admission and seasonal variations in hospitalizations for heart failure

Abstract: Aims: To investigate the annual hospitalization rate and seasonal variation in confirmed heart failure (HF) admissions. Methods and Results: Records from all admissions to one hospital during 1 year with a HF diagnostic code were reviewed. From 1953 admissions, 595 were excluded because they did not fulfill the diagnostic criteria. A total of 1069 patients had 1358 admissions with confirmed HF. Mean age was 74.8"11.5 years, 42% were males. The admission data were matched with data from the municipal census wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
52
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 23 publications
9
52
1
2
Order By: Relevance
“…A similar seasonal variation has been reported from European countries. [31][32][33] Although the precise reasons for this variation remain unknown, a potential explanation might be the presence of some other condition with a well-known seasonal variation such as respiratory tract infection, myocardial infarction and ischemia, or high blood pressure. Heart rate and systemic blood pressure have been reported to rise in cold environments, thus increasing cardiac oxygen consumption and cardiac afterload.…”
Section: Discussionmentioning
confidence: 99%
“…A similar seasonal variation has been reported from European countries. [31][32][33] Although the precise reasons for this variation remain unknown, a potential explanation might be the presence of some other condition with a well-known seasonal variation such as respiratory tract infection, myocardial infarction and ischemia, or high blood pressure. Heart rate and systemic blood pressure have been reported to rise in cold environments, thus increasing cardiac oxygen consumption and cardiac afterload.…”
Section: Discussionmentioning
confidence: 99%
“…Martínez-Sellés et al found a higher rate of hospitalization of males aged <80 years and females aged ≥80 years. 10 Kaneko et al 27 reported that patients with preserved EF, older age, hypertension, and CS1 were susceptible to winter admission of AHF. They emphasized the importance of BP control during…”
Section: Clinical Characteristics Of Cs1 Patients With Winter Onset Omentioning
confidence: 99%
“…1 Similar strong seasonal peaks in admissions to hospital have also been observed in relation to heart failure. [2][3][4][5] Counter-intuitively, the seasonal pattern is strongest in regions with warmer climates. 6,7 For example, a strong association between relatively cold temperatures and cardiovascular disease was found in Newcastle, Australia, but no association was found in three populations in Finland.…”
mentioning
confidence: 99%
“…6,7 For example, a strong association between relatively cold temperatures and cardiovascular disease was found in Newcastle, Australia, but no association was found in three populations in Finland. 1 Winter increases in heart failure (HF) admissions have been found in France, 2 Spain, 3 Scotland, 4 Japan, 5 and Argentina. 8 In France, HF deaths were 20% above average in January and 15% below average in August.…”
mentioning
confidence: 99%